2021
DOI: 10.3390/cancers13010145
|View full text |Cite
|
Sign up to set email alerts
|

Use of Palliative Chemotherapy and ICU Admissions in Gastric and Esophageal Cancer Patients in the Last Phase of Life: A Nationwide Observational Study

Abstract: Since intensive care unit (ICU) admission and chemotherapy use near death impair the quality of life, we studied the prevalence of both and their correlation with hospital volume in incurable gastroesophageal cancer patients as both impair the quality of life. We analyzed all Dutch patients with incurable gastroesophageal cancer who died in 2017–2018. National insurance claims data were used to determine the prevalence of ICU admission and chemotherapy use (stratified on previous chemotherapy treatment) at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…In a cross-national European end of life study in cancer and non-cancer patients from general practitioners, hospital death rates were lowest for Dutch patients (28%), and highest for Italian patients (39%) [ 24 ]. We reported a hospital death rate of 25% (4% in the ICU), comparable to the rate in a recent Dutch insurance data study in upper gastro-intestinal (GI) cancer patients of whom 23% died in the hospital [ 25 ]. In metastatic breast cancer, one French and one US study reported in-hospital death rates of 70% [ 21 ] and 19% [ 26 ], respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a cross-national European end of life study in cancer and non-cancer patients from general practitioners, hospital death rates were lowest for Dutch patients (28%), and highest for Italian patients (39%) [ 24 ]. We reported a hospital death rate of 25% (4% in the ICU), comparable to the rate in a recent Dutch insurance data study in upper gastro-intestinal (GI) cancer patients of whom 23% died in the hospital [ 25 ]. In metastatic breast cancer, one French and one US study reported in-hospital death rates of 70% [ 21 ] and 19% [ 26 ], respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Other factors related to more chemotherapy prescriptions shortly before death in ABC were younger age [ 29 , 30 ], higher albumin levels [ 29 ], greater disease burden [ 30 ], more prior lines of chemotherapy [ 30 ], and in this study we found HR−/HER2− breast cancer, and survival time <1 year as related factors. Larger hospital size was associated with fewer chemotherapy prescription shortly before death in the Dutch GI cancer study [ 25 ]. Chemotherapy prescription shortly before death is associated with less palliative care, and more death in the hospital [ 21 , 32 ], the latter also being observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A comparable registry-based analysis of chemotherapy use near the end-of-life in patients with gastroesophageal cancer, also performed in the Netherlands, reported slightly lower percentages of chemotherapy use in the last 3 and last month of life compared to our study [20]. ICU admissions were rare in both patient populations.…”
Section: Discussionsupporting
confidence: 47%
“…Congruently, patients preferring not to know prognosis more often reported optimism, known to relate to fighting spirit, as a reason for wanting limited information [ 67 ]. Still, physicians should evaluate the adaptiveness of patients’ prognostic unawareness based on strong fighting spirit, since it may obstruct anticipation of the end-of-life [ 9 , 68 ]. Considering that patients’ readiness for prognostic discussions could evolve over time, physicians may need to explore patients’ prognostic information preferences repeatedly (e.g., “Some people like to know everything about their illness and what may happen in the future, others prefer not to know too many details.…”
Section: Discussionmentioning
confidence: 99%